Ancient petrified time capsules of knowledge – the fossil collections of Lund University, Sweden - Ahlberg, Per; Eriksson, Mats (GFF, 2025)
Natural history collections hold immense global significance – not only as historical archives but also as precious resources for novel scientific discoveries. These collections, housed in museums and institutions worldwide, are (or should be) accessible and open for study. In this paper, we provide a brief history of the fossil collections at Lund University, Sweden, tracing their origins, key historical contributors, contents, significance and current state, as well as their future prospects. The collections’ foundation dates back to 1735 when Kilian Stobæus (1690–1742) bequeathed his extensive assembly of artefacts to the university, which originally included several thousand geological specimens, such as fossils, minerals, rocks and soil samples. Since then, the Lund collections have steadily expanded through contributions from numerous influential Earth science scholars. However, they have also undergone a convoluted history, including multiple relocations, all of which is outlined herein. Beyond documenting the Lund fossil collections, we highlight the broader importance of natural history collections, particularly with regard to type material. Despite their critical role in research and education, these collections in many cases remain undervalued by both the public and policymakers, resulting in insufficient financial support for their curation. This neglect poses an uncertain but likely detrimental impact on scientific and cultural heritage. As stewards of these valuable resources, we have a responsibility to preserve and develop them for future generations.